Implementation of Legal Protection for the Poor to Get Health Services - Sandika Sandika; Fitria Esfandiari; Catur Wido Haruni (Indonesian Journal of Law and Policy Studies, 2022)
ABSTRACT Legal protection of health services for poor patients is directed to be able to apply the principles of a comprehensive, integrated, equitable, and affordable. This is principally stated in Law 36/2009 on Health. However, services in the health sector as one of the implementations of legal protection, especially for the poor, are still not optimal. To overcome these problems, the authors provide two problem formulations, namely how the implementation of legal protection for the poor to obtain health services and how the government's efforts to provide legal protection for the poor to obtain health services. The research method used is a sociological juridical approach. Sources of data include primary and secondary data, data collection through interviews and further analysis. Based on the results of research and discussion, namely: First, the implementation of legal protection for the poor for health services has not run optimally. This is often found in the behavior of doctors who are less professional in serving the poor. Second, the government's efforts to provide protection to the poor have been implemented. One of them is the issuance of a health insurance card. This effort has a significant impact in its implementation so that it is more proactive in responding to health service problems experienced by poor patients.